2012
DOI: 10.1016/j.socec.2011.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Social norms and tax compliance: Framing the decision to pay tax

Abstract: Observed levels of tax compliance are higher than predicted levels (when predictions are based on Allingham and Sandmo's neoclassical model of tax evasion). They are higher if social norms recognise the importance of compliance. But how do social norms frame decisions to pay tax? Can prospect theory be applied to shed insight into the way that social norms exert their influence? An analysis of questionnaire responses (from Italy and from the UK) suggests that they exert their influence by changing the referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 28 publications
3
41
0
2
Order By: Relevance
“…In his research on taxpayers in Malaysia, Hai and See (2011) proved that subjective norm positive effect on tax compliance intentions. Similar results were shown by Cullis, Jones and Savoia (2012) were able to show that social norms will lead intention to comply. Mustikasari (2007) has also been proved empirically that subjective norms positively affect tax compliance intentions.…”
Section: H 1 : Perception Taxpayer Government Has Positive Influence supporting
confidence: 86%
“…In his research on taxpayers in Malaysia, Hai and See (2011) proved that subjective norm positive effect on tax compliance intentions. Similar results were shown by Cullis, Jones and Savoia (2012) were able to show that social norms will lead intention to comply. Mustikasari (2007) has also been proved empirically that subjective norms positively affect tax compliance intentions.…”
Section: H 1 : Perception Taxpayer Government Has Positive Influence supporting
confidence: 86%
“…In this case, the reference point would be the difference between the expected tax liability and the taxes paid in advance. In a recent study, Cullis et al (2012) suggest that social norms may lead to an aspiration level. 6…”
Section: Figure 1: Tax Evasion Under Prospect Theorymentioning
confidence: 99%
“…An individual taxpayer to comply with their tax obligations is closely linked to his/her ethical values. Previous study by Cullis, Jones and Savoia (2012) suggested that social norms influenced one's ethical belief mainly in two ways -internal mediation, which focuses on the intrinsic value derived from being "true to oneself", and external mediation, which focuses on the intrinsic value derived from conforming to group behaviour. Ho et al (2013) find that a majority of Chinese taxpayers agree with Lawrence Kohlberg's concept of the stages of moral development (Crain, 2005).…”
Section: Ethical Perceptionmentioning
confidence: 99%